RECOMMENDED PRODUCTS FOR AN ONLINE SHOP AMONG INDONESIAN STUDENT USERS - Rianto; Wibowo, Adityo Permana (University Of Technology Yogyakarta, 2019)
Electronic commerce is a website category that has tremendous growth. As an impact of the growth is information flooding for users, especially on product category. Therefore, the recommended products for online shops are important. This study aimed to develop recommended products for online shops that may enhance successful transactions in electronic commerce. This study involved 100 students that have been experienced in online transactions using a survey method. Data were analyzed using the Friedman Test and Weight Mean Score to obtain the highest level of product recommendation. The results indicated that fashion and shoes are the most recommended products for online shops in student groups of users.